2017
DOI: 10.1111/cmi.12749
|View full text |Cite
|
Sign up to set email alerts
|

A novel dense granule protein, GRA41, regulates timing of egress and calcium sensitivity inToxoplasma gondii

Abstract: SUMMARY Toxoplasma gondii is an obligate intracellular apicomplexan parasite with high seroprevalence in humans. Repeated lytic cycles of invasion, replication and egress drive both the propagation and the virulence of this parasite. Key steps in this cycle, including invasion and egress, depend on tightly regulated calcium fluxes and, while many of the calcium-dependent effectors have been identified, the factors that detect and regulate the calcium fluxes are mostly unknown. To address this knowledge gap, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 73 publications
0
41
0
Order By: Relevance
“…Plaque and doubling assays were performed with 12-well plates using standard methods (50). Briefly, for the plaque assays, 500 freshly egressed parasites were added to confluent HFF monolayers.…”
Section: Methodsmentioning
confidence: 99%
“…Plaque and doubling assays were performed with 12-well plates using standard methods (50). Briefly, for the plaque assays, 500 freshly egressed parasites were added to confluent HFF monolayers.…”
Section: Methodsmentioning
confidence: 99%
“…This protein localizes within a recognized candidate for Ca 2+ storage, the TVN. The TVN is also known to be crucial for T. gondii cellular cycle regulation inside the PV, and the absence of GRA41 results in altered morphology of this structure [ 33 ].…”
Section: Egress Signallingmentioning
confidence: 99%
“…As for GRA41, a recent study showed that a mutation in this dense granule protein results in aberrations of parasite calcium levels and egress. Parasites lacking GRA41 exhibit dysregulation of calcium ion uptake, leading to altered calcium ion homeostasis and premature egress ( 39 ). Although LCAT and GRA41 appear to affect egress in opposite ways, they both reside in the PV, suggesting an emerging role for PV resident proteins in Toxoplasma egress.…”
Section: Discussionmentioning
confidence: 99%